Transcription elongation defects link oncogenic SF3B1 mutations to targetable alterations in chromatin landscape - Boddu, Prajwal C.; Gupta, Abhishek K.; Roy, Rahul; De La Peña Avalos, Bárbara; Olazabal-Herrero, Anne; Neuenkirchen, Nils; Zimmer, Joshua T.; Chandhok, Namrata S.; King, Darren; Nannya, Yasuhito; Ogawa, Seishi; Lin, Haifan; et al. (Molecular cell, 2024)
Transcription and splicing of pre-messenger RNA are closely coordinated, but how this functional coupling is disrupted in human diseases remains unexplored. Using isogenic cell lines, patient samples, and a mutant mouse model, we investigated how cancer-associated mutations in SF3B1 alter transcription. We found that these mutations reduce the elongation rate of RNA polymerase II (RNAPII) along gene bodies and its density at promoters. The elongation defect results from disrupted pre-spliceosome assembly due to impaired protein-protein interactions of mutant SF3B1. The decreased promoter-proximal RNAPII density reduces both chromatin accessibility and H3K4me3 marks at promoters. Through an unbiased screen, we identified epigenetic factors in the Sin3/HDAC/H3K4me pathway, which, when modulated, reverse both transcription and chromatin changes. Our findings reveal how splicing factor mutant states behave functionally as epigenetic disorders through impaired transcription-related changes to the chromatin landscape. We also present a rationale for targeting the Sin3/HDAC complex as a therapeutic strategy. [Display omitted] •SF3B1 oncogenic mutations reduce RNAPII gene-body elongation rate and promoter density•RNAPII elongation defect is linked to disruption of the early spliceosome assembly•Chromatin landscape is altered, rendering these functionally epigenetic disorders•Sin3/HDAC pathway can be therapeutically targeted in SF3B1 mutant disease Boddu et al. reveal how common cancer-associated mutations in SF3B1, a core splicing factor, alter RNAPII transcription kinetics through impaired early spliceosome assembly. Transcription defects alter chromatin organization at gene promoters, which can be reversed by inhibiting the Sin3/HDAC complex, providing a potential therapeutic strategy.